2010
DOI: 10.4102/sajs.v106i9/10.310
|View full text |Cite
|
Sign up to set email alerts
|

Palladium mixed-metal surface-modified AB<sub>5</sub>-type intermetallides enhance hydrogen sorption kinetics

Abstract: Surface engineering approaches were adopted in the preparation of advanced hydrogen sorption materials, based on 'low-temperature', AB 5 -type intermetallides. The approaches investigated included micro-encapsulation with palladium and mixed-metal mantles using electroless plating. The influence of micro-encapsulation on the surface morphology and kinetics of hydrogen charging were investigated. It was found that palladium-nickel (Pd-Ni) co-deposition by electroless plating significantly improved the kinetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…XRD studies of the substrate alloy (see [34] for more details) showed that the material contains a major CaCu 5 -type intermetallic phase with the periods of hexagonal unit cell a = 5.00295(1)Å, c = 4.05111(2)Å. The XRD pattern also showed the presence of trace amounts of a mixed rare-earth-nickel oxide (RE 2 NiO 4 ), most probably originating from the surface oxidation of the material.…”
Section: Surface-modified Ab 5 -Type Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…XRD studies of the substrate alloy (see [34] for more details) showed that the material contains a major CaCu 5 -type intermetallic phase with the periods of hexagonal unit cell a = 5.00295(1)Å, c = 4.05111(2)Å. The XRD pattern also showed the presence of trace amounts of a mixed rare-earth-nickel oxide (RE 2 NiO 4 ), most probably originating from the surface oxidation of the material.…”
Section: Surface-modified Ab 5 -Type Materialsmentioning
confidence: 99%
“…Further details on the preparation and characterisation of the surface-modified MH materials are discussed elsewhere [27][28][29][30][31][32][33][34]. Experimental details on hydrogen absorption from gas mixtures will be presented in Section 3.2.…”
Section: Figmentioning
confidence: 99%
“…The hydrogenation kinetic curves are presented in Figure 4 . In addition, Table 2 presents the results obtained through fitting of the experimental data on the Avrami–Erofeev model, which is described here [ 17 ]. Without vacuum activation, the uncoated TiMn 1.52 alloy exhibits slow hydrogen absorption, accompanied by a long incubation period of ~5 min.…”
Section: Resultsmentioning
confidence: 99%
“…Surface modification of the TiMn 1.52 alloy was conducted through autocatalytic deposition of Pd in a hypophosphite-based autocatalytic plating bath following the procedure described here [ 17 ]. Prior to palladium deposition, the materials were first sensitized and activated in a palladium–tin (Pd–Sn) colloidal solution [ 17 ] resulting in increased densities of Pd deposition and surface Pd loading on the intermetallide. The activated intermetallide was subsequently suspended in the palladium plating bath.…”
Section: Experimental Methodsmentioning
confidence: 99%
“…Nevertheless, more energy associated with hydrogen compression is not economically favoured [3]. The most promising way is to store hydrogen in solid absorbents, such as metal alloys in which hydrogen bound to these materials to form metal hydrides [4]. An attractive feature of solid-state storage is that the absorption of hydrogen using many of these metal alloy materials is reversible, thereby reducing operational costs [5].…”
Section: Introductionmentioning
confidence: 99%